The effect of financial behavior, financial literacy, and macroeconomics on stock investment decision-making in East Nusa Tenggara - Ni Nyoman Alit Nugraheni; Pius Bumi Kellen; Petrus Emanuel de Rozari (goodwood publishing, 2022)
Purpose: This study discusses the influence of financial behavior, financial literacy, and macroeconomics on stock investment decision-making in East Nusa Tenggara. Research Methodology: This research is associative research with a quantitative approach. Distributing questionnaires to 225 investors who were used as research samples collected research data. The data obtained were analyzed by multiple linear regression analysis. Results: Partially or simultaneously independent variables affect the dependent variable in the form of investment decisions positively and significantly. Only financial literacy does not have a significant influence on investment decisions Limitations: This research was conducted during the Covid-19 pandemic, where everything that was done in this research was done without meeting directly with the informants. In addition, the variables studied in this study are dynamic and complex in which the results and thoughts can change at any time according to existing conditions. Contribution: This research becomes scientific information about investor behavior in making investment decisions specifically in the East Nusa Tenggara region.